(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
The article focuses on problems connected with mergers in financial sector. Itpresents different forms of mergers in banking and aims of mergers. The paper alsocharacterizes the process of consolidation in the banking system in Poland and the levelof concentration of markets in other EC countries.